BASIC AND CLINICAL STUDIES ON CEFDINIR - MORITA, MASAYUKI; MATSUMOTO, FUMIO; IMAI, TAKEO; KOKUBU, KATSUYA; HOJO, TOSHIO; SAKURAI, IWAO; TAURA, YUJI; TAKAHASHI, TAKAYUKI (CHEMOTHERAPY, 1989)
We studied the antibacterial activity, absorption, excretion and clinical efficacy on cefdinir (CFDN), a new oral cephalosporin, and obtained the following results. 1. Antibacterial activity: the antibacterial activity of CFDN against 25 clinical isolates each of 5 organisms was investigated. CFDN had a broad- spectrum activity against Gram-positive and-negative organisms, and the MIC90s against Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis and methicillin-resistant S. aureus were 6.25, 1.56, 1.56, 1.56 and 50μg/ml, respectively. 2. Absorption and excretion: in adult and elderly subjects, the peak plasma concentrations of CFDN were 1.51 and 1.15μg/ml, respectively, 3-4 hours after a single oral administration of 200mg; the plasma half-lives were 1.76 and 1.90h, and the plasma concentrations at 12 h after dosing were 0.11 and 0.08μg/ml. In elderly subjects administered 100mg of CFDN the plasma concentration was 0.85μg/ml 3h. after administration with a plasma half-life of 1.76 h. The plasma concentration at 12 h after dosing was 0.035μg/ml. The 12-h urinary recovery rate was 16-26%. The peak sputum concentrations ranged from 0.057-0.088μg/ml in 2 patients with bronchial asthma after a single dose of 200mg. 3. Clinical evaluation: CFDN was administered orally at 100 and 200mg 2 or 3 times a day to 24 patients with respiratory tract infections. The clinical response was good in 22 cases and fair and poor in 1 each. A side effect, light headedness, was observed in one case, but no abnormal value was noted.